THE WELFARE TRADITIONS IN INDONESIA: TRACKING THE ISLAMIC WELFARE SERVICES OF NAHDLATUL ULAMA - Fata, Badrus Samsul; Rosyadi, Imron (AL Fikrah: Jurnal Pemikiran dan Pendidikan Islam, 2026)
This article meticulously tracks the legacies of Nahdlatul Ulama (NU) in shaping the religious welfare traditions of Indonesia. It explores the deep theological foundations and sophisticated institutional mechanisms of NU’s social activism, revealing a resilient and adaptive faith-based welfare ecosystem. The analysis demonstrates that NU’s contributions are not merely ad-hoc charitable acts but a systematic, ideologically coherent effort to realize the principles of social justice embedded in the Ahlussunnah wal Jama’ah tradition. The study confirms that NU’s strength lies in its ability to synthesize traditional religious authority with modern organizational strategies. The pesantren serves as the cultural and spiritual heart of its welfare network, while the expansion of higher education and the professionalization of healthcare represent a strategic engagement with modernity. The article also highlights the inherent challenges NU faces, including the tension between tradition and bureaucracy, the need for greater financial transparency, and its complex relationship with the state. By providing a comprehensive analysis of NU’s welfare model, this study contributes to a deeper understanding of the interplay between religion, social welfare, and national development in Indonesia.